Inovasi Wakaf Produktif Berbasis CWLD: Studi Kasus Sentra Jamur Sragen - Fanny Luthffiana Anisa; Witia Oktaviani (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2025)
This research aims to analyze the effectiveness of Cash Waqf Link Deposit (CWLD) as a means of collecting productive waqf funds at the Sentra Jamur Sragen. This study focuses on CWLD practices and productive waqf from an Islamic perspective, as well as the implications of productive waqf for waqf donors and the surrounding community. The research methodology uses a descriptive qualitative approach with a case study approach. This method was chosen to provide an in-depth description of the CWLD strategy implemented at Bank Syariah Sragen, productive waqf practices at the Sentra Jamur Sragen, and the implications of productive waqf practices. The results of this study indicate that CWLD is the right choice for collecting waqf funds to carry out productive waqf because CWLD-based fund collection is considered transparent, fast, and effective. In addition, CWLD and productive waqf practices are considered to be in accordance with Islamic law applicable in Indonesia and in accordance with regulations set by the government. Furthermore, waqf donors and the surrounding community feel the positive impact of the Sentra Jamur Sragen.